2014
DOI: 10.1155/2014/260209
|View full text |Cite
|
Sign up to set email alerts
|

Kalman Filter for Cross-Noise in the Integration of SINS and DVL

Abstract: The integration of strapdown inertial navigation system and Doppler velocity log (SINS/DVL) is widely used for navigation in automatic underwater vehicles (AUVs). In the integration of SINS/DVL, the velocity measured by DVL in body frame should be projected into navigation frame with the help of attitude matrix calculated by SINS to participate in data fusion. In the process of data fusion based on standard Kalman filter, the errors in calculated attitude matrix are characterized by state variance and process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 11 publications
(48 reference statements)
0
24
0
Order By: Relevance
“…To shorten the length of this paper, the characteristics of the MCP and PS measurements are not given in detail but can be found in [5,6,12].…”
Section: Error Propagation Models Of Mcp and Psmentioning
confidence: 99%
See 2 more Smart Citations
“…To shorten the length of this paper, the characteristics of the MCP and PS measurements are not given in detail but can be found in [5,6,12].…”
Section: Error Propagation Models Of Mcp and Psmentioning
confidence: 99%
“…From the projection process V n DVL " C n b V b DVL , it can be observed that there is cross-noise between C n b and V b DVL . In this paper, the enlarged variance of V is used to include the crossed noise, and more details to address this noise can be found in [12]. In the following sections, this noise is not considered, and SINS and DVL are assumed to be independent.…”
Section: System and Measurement Equations Of Sins/dvlmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the velocity correction algorithm of a DVLaided inertial navigation system (INS) employs a loosely coupled approach that uses the body frame velocities calculated by the DVL as the input to the Kalman filter. There has been more research on loosely coupled approaches than tightly coupled ones, and these have focused on designing and verifying navigation filters based mostly on the extended Kalman filter [3][4][5][6]. Recent design and verification studies have also used other types of filters such as the unscented Kalman filter and cubature Kalman filter [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Now the integrated navigation system which consists of multiple navigation sensors is widely adopted on underwater vehicles [6][7][8]. As a high-precision velocity measuring instrument, the Doppler velocity log (DVL) has become increasingly popular as the fundamental component of underwater integrated navigation systems [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%